AMBITION IN LOVE IN NICHOLAS SPARKS’ NOVEL THE NOTEBOOK - Laowo, Jojo Krisman; Pardi, Pardi (JOURNAL OF LANGUAGE, 2024)
This article examines how the first character by the name of Noah Calhoun in Nicholas Sparks' novel, The Notebook, passionately pursues love-driven ambition. Ambition here means having strong determination to achieve personal goals. It is a central theme in the protagonist's journey. Using a descriptive qualitative approach, this study carefully looks at Noah's various efforts to find love, using ideas from Bridge and Krutus. He sees ambition as a powerful force that drives people to achieve great things. Through this method, the research explores how the protagonist's ambitions in love unfold, showing a deep dive into human hopes and emotions. The study reveals Noah 's ambitious actions in his pursuit of Allie. It shows how he writes letters to her, builds their dream home, and works to bring back her memories. Noah's unwavering dedication and determination showcase his strong love, leading to a heartwarming conclusion where love conquers all obstacles. Overall, this research sheds light on the role of ambition in romantic relationships, highlighting Noah's steadfast pursuit of love amidst life's challenges. His resilience reminds us of how ambition can shape our relationships and stories.